Garcia, Joe (2010): The Secret Web of Intrigue - Ferrer Gallardo, Xavier (Documents d’Anàlisi Geogràfica, 2012)
Garcia, Joe (2010) The Secret Web of Intrigue Gibraltar: Panorama Publishing ISBN: 978-0-9583026-0-9